Interferon‐γ Receptor 1 and GluR1 upregulated in motor neurons of symptomatic hSOD1G93A mice. (27th December 2018) - Sengupta, Saikata; Le, Thanh Tu; Adam, Adam; Tadić, Vedrana; Stubendorff, Beatrice; Keiner, Silke; Kloss, Linda; Prell, Tino; Witte, Otto W.; Grosskreutz, Julian
Abstract: Motor neurons are markedly vulnerable to excitotoxicity mostly by alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic receptor (AMPAR) stimulation and are principal targets in the neurodegenerative disease Amyotrophic Lateral Sclerosis. Interferon‐gamma (IFN‐γ), a pro‐inflammatory cytokine, can independently cause neuronal dysfunction by triggering calcium influx through a calcium‐permeable complex of IFN‐γ receptor 1(IFNGR1) subunit and AMPAR subunit GluR1. This receptor complex is formed via a non‐canonical neuron‐specific IFN‐γ pathway that involves Jak1/Stat1 and Protein Kinase A. In this study, we explore the expression of the pathway's participants for the first time in the hSOD1G93A Amyotrophic Lateral Sclerosis mouse model. Elevated IFNGR1 and GluR1 are detected in motor neurons of hSOD1G93A symptomatic mice ex vivo, unlike the downstream targets ‐ Jak1, Stat1, and Protein Kinase A. We, also, determine effects of IFN‐γ alone or in the presence of an excitotoxic agent, kainate, on motor neuron survival in vitro. IFN‐γ induces neuronal damage, but does not influence kainate‐mediated excitotoxicity. Increased IFNGR1 can most likely sensitize motor neurons to excitotoxic insults involving GluR1 and/or pathways mediated by IFN‐γ, thus, serving as a potential direct link between neurodegeneration and inflammation in Amyotrophic Lateral Sclerosis. Abstract : In this study, we examine a non‐canonical, neuron‐specific IFN‐gamma pathway in hSOD1G93A motor neurons. The upstream targets IFNGR1 and GluR1, subunits of Interferon‐Gamma receptor and AMPAR respectively, are upregulated in motor neurons of hSOD1G93A mice. In contrast, the expression of key downstream participants—Jak1, Stat1, and Protein Kinase A, are not enhanced. Functional studies of the pathway in vitro demonstrated neuronal damage most likely from calcium ion influx.